ELECTROMAGNETIC VIBRATION DISTURBING FORCES AT THE ECCENTRICITY OF ROTOR OF TURBOGENERATOR - Vaskovskyi, Yu. M.; Melnyk, A. M.; Tytko, O. I. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2016)
Electromagnetic vibration disturbing forces in different variants of the rotor displacement from an axis of the stator bore is carried out. Investigation for ТG type ТGV-200-2 by finite element method in COMSOL Multiphysics is carried out. The field mathematical model of static and dynamic eccentricity is described. The amplitude vibration disturbing forces are greatest, when a static eccentricity direction coincides with an axis of the stator winding phase is shown. The diagnostic features static and dynamic eccentricities are formulated. The most value of forces in the point with minimal air gap is shown. The diagnostic features static and dynamic eccentricities and the method of diagnostic eccentricity are formulated. Diagnostic feature of static eccentricity is to change the amplitude Maxwell stress tensor is established. The dynamic eccentricity diagnostic features are appearance in the spectrum of vibration disturbing forces rotating and multiple harmonics.